Analyzing consumer purchase decisions through a gender perspective at Cafe Daja House - Mahadewi, Anisa Agatha; Ahmad, Aripin (Asian Journal of Economics and Business Management, 2025)
Consumer purchasing decision making at Cafe Daja House is a process that involves various considerations, starting from recognizing needs, searching for information, to evaluating alternatives. An important factor in this process is gender differences, where men and women tend to have different approaches in making purchasing decisions. Men generally focus more on functional and price aspects, while women are more influenced by emotional and aesthetic factors. The question is Does gender perspective influence purchasing decisions at Cafe Daja House in Bandar Lampung. To answer this question, data was collected through a survey involving 100 samples. By using the Multiple Regression Statistical Model, it turns out that Female Gender and Male Gender influence Purchasing Decisions at Cafe Daja House in Bandar Lampung. The magnitude of this influence is 45.30%, which means that the Gender Perspective variable (X) is able to influence purchasing decisions at Cafe Daja House by 45.30%. For this reason, it is expected to periodically change the atmosphere of the environment according to the circumstances and activities that are always conveyed through promotions.